Date: 09/12/2001 at 08:26:08
From: Doctor Rick
Subject: Re: Why does - (-a) = a
Hi, Eduardo.
We can start with how -a is defined. It is "the additive inverse of a"
- that is, it is the number that, when added to a, gives 0:
a + -a = 0
Therefore -(-a) means the number that, when added to -a, gives 0. But
applying the commutative property of addition, the equation above
becomes
-a + a = 0
Therefore the number that, when added to -a, gives 0 is a; or,
-(-a) = a
A closely related, but different, question is how we can prove that
-1 * -1 = 1
The theorem linking these two is this:
-1 * a = -a
Let's prove this. Start with the fact that zero times any number is
zero:
0 * a = 0
Write 0 as (1 + -1), which follows from the definition of -1.
(1 + -1)*a = 0
Apply the distributive property:
1*a + -1*a = 0
Use the fact that 1 times any number is the same number:
a + -1*a = 0
Now, the number that, when added to a, gives 0 is -a. Therefore
-a = -1*a
Using this theorem, we can easily prove that -1 times -1 is 1:
-1 * -1 = -(-1)
= 1
For other approaches to the question of why a negative times a
negative is positive (both informal illustrations and formal proofs),
see our Dr. Math FAQ, "Negative times a negative":
http://mathforum.org/dr.math/faq/faq.negxneg.html
- Doctor Rick, The Math Forum
http://mathforum.org/dr.math/